2020
DOI: 10.11646/zootaxa.4809.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater lampreys and fishes of Turkey; a revised and updated annotated checklist 2020

Abstract: The current status of the inland waters ichthyofauna of Turkey is revised, and an updated checklist of the freshwater fishes is presented. The latest checklist included all species listed in the available previous study that was published in 2015, which is now updated after a period of five years. We revised the validity of previously accepted species and added newly described and reported species in Turkey. Some previously erroneously reported species and not established alien fishes were excluded fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 0 publications
2
44
0
2
Order By: Relevance
“…Some diadromous fish species in the aquatic system are; Salmo trutta labrax, Acipencer stellatus, Acipenser gueldenstaedtii, Huso huso, Anguilla anguilla, Atherina boyeri, Lampetra lanceolata, Alosa fallax, Mugil cephalus and Platichthys flesus, etc. (Çiçek et al, 2018;Ekmekçi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some diadromous fish species in the aquatic system are; Salmo trutta labrax, Acipencer stellatus, Acipenser gueldenstaedtii, Huso huso, Anguilla anguilla, Atherina boyeri, Lampetra lanceolata, Alosa fallax, Mugil cephalus and Platichthys flesus, etc. (Çiçek et al, 2018;Ekmekçi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At least 18 species of the genus Cobitis belonging to Cobitidae are known in Turkey. It was reported that an endemic C. phrygica distributes in Acıgöl, Salda and Söğüt lakes watersheds of Turkey (Fricke et al 2007, Kuru et al 2014, Çiçek et al 2015 and an endemic C. simplicispina distributes in the Sakarya and Kızılırmak basins and around the Tuz lake (Erk akan et al 2003). Also, some localities of C. simplicispina were recorded from Denizli and Muğla provinces (Yılmaz et al 2006, Güçlü et al 2013.…”
mentioning
confidence: 99%
“…Geldiay & Balık (2007)'a göre bu iki türden B. plebejus escherichi'nin doğal yayılış alanının Ege ve Batı Anadolu iç suları olduğu ve Ekingen & Sarıeyyüpoğlu (1981)'nun çalışmasında bu türe ait verilerin Güney ve Güney Doğu Anadolu Bölgesi olarak verilmesi bir hata olarak görülmektedir (Yıldırım et al, 2015). Söz konusu çalışmada verilen bu iki türe bizim çalışmamızda rastlanmadığı gibi Dicle-Fırat nehir sisteminde yapılan diğer faunistik çalışmalarda da rastlanmamıştır (Birecikligil & Çiçek, 2010;Çiçek et al, 2015). Muhtemelen yapılan bir hatadan dolayı bildirilen türün Barbus lacerta olabileceği daha sonra yapılan çalışmalarda görülmektedir (Yıldırım et al, 2015).…”
Section: Discussionunclassified